Development of mathematical model for estimation of wetting front advance under drip irrigation in sandy loam soil - TIRKEY, SHRUTI RANI; SHERRING, ARPAN; KUMAR, MUKESH (Journal of Soil and Water Conservation, 2020)
Experiment was conducted to determine wetting front dimensions in drip irrigation and to establish relationship between emitter discharge and wetting front movement. Dimension of wetting front in horizontal direction and vertical direction for 2 LPH and 4 LPH emitter discharges at 30 min, 60 min, 90 min, 120 min, 150 min and 180 min duration of water application were estimated in sandy loam soil. The result shows that vertical distance of wetting front was increasing very rapidly in the beginning but slowly at later stages. Mathematical equation was developed for the estimation of dimension of wetting front in horizontal direction and vertical direction. The developed mathematical equations for dripper discharge of 2 LPH for estimation of dimension of wetting front advance in horizontal and vertical direction showed strong correlation (R2=0.99) between calculated and measured values. The developed mathematical equations for dripper discharge of 4 LPH for estimation of dimension of wetting front advance in horizontal direction and vertical direction also showed strong relationship (R2=0.98). These mathematical models can be used efficiently to predict the horizontal and vertical movement of wetting front for the sound design of drip irrigation system and can also be used in precision irrigation for various crops to match their varying root zone temporally. The matching of the root zone for different crops will lead to optimal utilization of nutrient and water uptake and thus will minimize the losses during irrigation.